Aggressive behaviour traits predict physiological stress responses in Nile tilapia (Oreochromis niloticus) - Barreto, Rodrigo Egydio [UNESP]; Volpato, Gilson Luiz [UNESP]; Faturi, Claudia de Brito; Giaquinto, Percilia Cardoso [UNESP]; de Freitas, Eliane Goncalves [UNESP]; de Castilho, Marisa Fernandes (Taylor & Francis Ltd, 2009)
This study tested whether aggressive behaviour can predict individual variation in stress responses of Nile tilapia Oreochromis niloticus. We used a mirror test to measure tendency to aggressive behaviour, and calculated the attack frequency and time until the first attack (latency) for each fish. One day later, we measured plasma cortisol and glucose, and two days later, we measured ventilatory frequency (VF) (pre-confinement responses). Immediately after the VF measure, we subjected the same fish to 30 min confinement, followed by measurements of cortisol, glucose, and VF (post-confinement responses). We found that post-confinement stress cortisol, glucose, and VF were higher than pre-confinement responses. Attack frequency was negatively correlated with VF and latency was positively correlated with baseline glucose and VF. Thus, we conclude that attack frequency and latency to a mirror reflection could be used to predict baseline levels of physiological stress indicators in Nile tilapia.
Keywords: stress; aggressive behaviour; physiological response; Glucocorticoid; carbohydrate; respiration; Nile tilapia; Oreochromis niloticus